2021
DOI: 10.1146/annurev-publhealth-090419-102204
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Social Needs in Health Care Settings: Evidence, Challenges, and Opportunities for Public Health

Abstract: There has been an explosion of interest in addressing social needs in health care settings. Some efforts, such as screening patients for social needs and connecting them to needed social services, are already in widespread practice. These and other major investments from the health care sector hint at the potential for new multisector collaborations to address social determinants of health and individual social needs. This article discusses the rapidly growing body of research describing the links between soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
110
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 88 publications
2
110
0
Order By: Relevance
“…Healthy social and professional integration such as anti-stigma campaigns for mental illness [ 42 ] could be considered to create a better social and environmental support for TDTs. By recognizing this group of people as valuable assets to the community and provide them equal opportunities, they could move at a faster rate towards a full social and professional life [ 43 ]. In addition, publishing the success stories of some patients could boost not only their self-esteem but also perhaps change the degree of stigmatization on them that is still present in some communities, just like in cases of AIDS and obesity [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Healthy social and professional integration such as anti-stigma campaigns for mental illness [ 42 ] could be considered to create a better social and environmental support for TDTs. By recognizing this group of people as valuable assets to the community and provide them equal opportunities, they could move at a faster rate towards a full social and professional life [ 43 ]. In addition, publishing the success stories of some patients could boost not only their self-esteem but also perhaps change the degree of stigmatization on them that is still present in some communities, just like in cases of AIDS and obesity [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simple and standardized approaches allow for patient self-administered screening; scalable pathways for responding to reported needs; population-level tracking of social needs; and consistent measures for program evaluation and research. Common questions in the US include screening for transportation, food insecurity, housing instability, utilities, and interpersonal violence [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the US have demonstrated the feasibility and patient acceptability of screening for social needs [ 21 22 74 75 ], as well as the need for further studies on the psychometric and pragmatic properties of various screening tools [ 76 ]. More research in the US and internationally is needed to evaluate the effectiveness and cost-effectiveness of social prescribing programs that link patients with community resources, particularly under different financing and governance structures [ 52 68 ]. However, evaluating integrated care efforts like social prescribing presents many challenges.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of programs nationwide aim to screen and connect families with desired social services. 8 , 9 Recent literature demonstrates low concordance between those who report social risk on screeners and those who desire resources, suggesting that offering social resources either before or in-place of screening may more effectively identify families who desire social assistance. 10 Considering this, Family Connects was intentionally designed without a screening component.…”
Section: Introductionmentioning
confidence: 99%